2019
DOI: 10.3390/agronomy9120800
|View full text |Cite
|
Sign up to set email alerts
|

Residual Distribution Kinetics of Pesticides in Cherry Tomato Peel, Pulp, and Fruit as a Function of Irrigation Water Salinity, Household Rinsing, and Storage Regimen

Abstract: The increased demand of high quantity and quality of cherry tomatoes requires the application of a wide range of pre-harvest pesticides. The application of dozens of pre-harvest pesticides frequently results in multiple pesticide residues, to which the end consumer is exposed. Incorrect usage of these pesticides may result in hazardous food contamination and therefore, it is crucial to monitor pesticide residues in pre- and post-marketed agricultural commodities. Hence, the objectives of the present study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Pyrimethanil, fludioxonil, cyprodinil and kresoxim-methyl were detected in different layers of apple fruit, and the highest concentrations were found in the apple peel [ 24 ]. Shimshoni et al indicated that the peel penetrability of difenoconazole and tetraconazole in cherry tomatoes was not dependent on the salinity level of the irrigation solution [ 25 ]. Utture et al described that azoxystrobin penetrated the internal parts of pomegranate fruit, while carbendazim and difenoconazole remained in the outer rind [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrimethanil, fludioxonil, cyprodinil and kresoxim-methyl were detected in different layers of apple fruit, and the highest concentrations were found in the apple peel [ 24 ]. Shimshoni et al indicated that the peel penetrability of difenoconazole and tetraconazole in cherry tomatoes was not dependent on the salinity level of the irrigation solution [ 25 ]. Utture et al described that azoxystrobin penetrated the internal parts of pomegranate fruit, while carbendazim and difenoconazole remained in the outer rind [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the relatively rapid decline in pesticide residues occurs within the pre-harvest period due to various environmental factors, their drop in post-harvest time can be slower and depends on the storage conditions ( https://ec.europa.eu/food/plant/pesticides_en ( European Commission ) ) . Furthermore, storage time and conditions such as temperature and humidity have been shown to have a major effect on fruit susceptibility to pests, on the accumulation of pesticide residues, and on fruit quality ( Shimshoni et al, 2019 ). Newly developed enhanced storage technologies and follow-up post-harvest protection, as well as technologies used to maintain high quality of fruit require an assessment of the impact of these technologies and products on the degradation of pesticide residues during the long-term storage ( Yigit and Velioglu, 2020 , Pandiselvam et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%